The value of a is 184. The above solution is derived using Pythagoras' theorem .
by using Pythagoras' theorem we will get 3 equations
now equating 1 and 3 equations we will get,
[tex]x^2 + 7^2 = 5^2 + (3+ (3- x))^2[/tex]
[tex]x^2 + 7^2 = 5^2 + (6^2+ x^2 + 12x)[/tex]
after solving this equation we get x = 1
now putting the value of x in equation 1 we get
[tex]r^2 = x^2 + 7^2\\r^2 = 1 + 49\\r^2 = 50[/tex]
now putting the value of r in equation 2 we get
[tex](3-x)^2 + (\frac{\sqrt{a}}{2}) ^2 = r^2[/tex]
[tex](3-1)^2 + (\frac{\sqrt{a}}{2}) ^2 = 50[/tex]
on solving the equation, we get
a = 184
To learn more about Pythagoras' theorem with the given link
https://brainly.com/question/343682
#SPJ4